The The Association between the Level of Glycosylated Hemoglobin and the Immunogenicity of the Rubella Vaccination: HgA1C Correlation with anti-rubella IgG - Haghighi, Mehrdad; Goudarzi, Mehdi; Sistanizad, Mohammad; Pourheidar, Elham (Novelty in Biomedicine, 2022)
Background: Diabetes mellitus (DM) can influence various aspects of the immune system that may alter the immune response to vaccines. Data about altering the immune response to the rubella vaccine in the presence of diabetes are not enough. We aimed to evaluate the association between the level of glycosylated hemoglobin (HbA1C) and the immunogenicity of the rubella vaccination. Materials and Methods: This cross-sectional retrospective study was conducted on the medical records of women who were tested to pre-pregnancy to check their antibody levels against rubella and had plasma levels of HbA1C. Results: During 3 years, 112 women with anti-Rubella IgG data were finally analyzed. The mean age±SD of participants was 32.10±4.87. According to the data, we detected no correlation between the plasma levels of HbA1C and IgG levels against rubella (Correlation Coefficient 0.219, p = 0.020). Conclusion: We revealed no correlation between the plasma levels of HbA1C and impaired immunogenicity of the rubella vaccination. We recommended a large-scale controlled clinical trial to evaluate the IgG levels against rubella in patients with high plasma levels of HbA1C compared to the control group.